PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE POCO 5G DI JAKARTA - Tumpal J.R. Sitinjak; Suryansah, Suryansah (Bajang Institute, 2024)
As the digital era advances, smartphones have become an essential and inseparable part of human life. This has triggered fierce competition in the smartphone market, where various brands continue to innovate, competing with each other for consumer attention and interest. The emergence of 5G smartphones has opened a new era in providing very high data access speeds, very low latency, and much wider network capacity. One of the 5G smartphone products circulating in Indonesia is the POCO 5G Smartphone. This study aims to examine the effect of product quality and price perceptions on purchasing decisions for POCO 5G smartphones in Jakarta. The data collection technique used in this research is a communication study through distributing electronic questionnaires based on Google Forms as a data collection tool for 100 respondents. The sampling technique used was non-probability sampling technique with a purposive sampling approach. The results showed that product quality and price perception had a positive and significant effect on purchasing decisions. The implication of this research is to look at the importance of the balance between product quality and price perception in influencing consumers to improve purchasing decisions